Inflammation and Renal Function after a Four-Year Follow-Up in Subjects with Unimpaired Glomerular Filtration Rate: Results from the Observational, Population-Based CARLA Cohort - Medenwald, Daniel; Girndt, Matthias; Loppnow, Harald; Kluttig, Alexander; Nuding, Sebastian; Tiller, Daniel; Thiery, Joachim J.; Greiser, Karin H.; Haerting, Johannes; Werdan, Karl (PloS one, 2014)
There is evidence that chronic inflammation is associated with the progression/development of chronic renal failure; however, relations in subjects with preserved renal function remain insufficiently understood. To examine the association of inflammation with the development of renal failure in a cohort of the elderly general population. After excluding subjects with reduced estimated glomerular filtration rate (eGFR<60 mL/min/1.73 m2) and missing data, the cohort incorporated 785 men and 659 women (aged 45-83 years). Follow-up was performed four years after baseline. Covariate adjusted linear and logistic regression models were used to assess the association of plasma/serum concentrations of soluble tumour necrosis factor receptor 1 (sTNF-R1), C-reactive protein (CRP), and interleukin 6 (IL-6) with change in eGFR/creatinine. The areas under the curve (AUCs) from receiver operating characteristics (ROCs) were estimated. In adjusted models sTNF-R1 was distinctively associated with a decline in eGFR in men (0.6 mL/min/1.73 m2 per 100 pg/mL sTNF-R1; 95% CI: 0.4-0.8), but not in women. A similar association could not be found for CRP or IL-6. Estimates of sTNF-R1 in the cross-sectional analyses were similar between sexes, while CRP and IL-6 were not relevantly associated with eGFR/creatinine. In the elderly male general population with preserved renal function sTNF-R1 predicts the development of renal failure.